Temporomandibular disorder, body pain and systemic diseases: Assessing their associations in adolescents - Braido, Guilherme Vinícius Do Vale [UNESP] (2020)
Painful temporomandibular disorders (TMD) in children and adolescents may impact negatively the individual´s life. The presence of comorbidities associated with TMD tends to increase the persistence of pain and to facilitate its chronification. Objective: To investigate the presence of other painful conditions and systemic diseases and their association with painful TMD. Methodology: In this cross-sectional study, 690 adolescents aged between 12-14 years old were evaluated through questionnaires and clinical examinations. Results: Painful TMD was found in 16.2% of the sample, with a significant association with bronchitis (OR= 2.5; p=0.003) and asthma (OR=3.1; p=0.013), reported by the parents/legal guardians of the participants. Adolescents with regional and widespread pain were 2.7 (95% CI: 1.65-4.55) and 3.6 (95% CI: 1.29-10.14) more likely to also present painful TMD. Painful TMD was associated with a higher number of body pain sites in the last 12 months (4.26 vs. 2.90; p<0.001), as well as a higher number of systemic diseases (1.48 vs. 1.18; p=0.048), when compared to adolescents without painful TMD. Conclusion: The findings of this study point out the importance of considering the presence of comorbid conditions in the diagnosis and management of painful TMD in adolescents. A multidisciplinary approach would contribute to better control of painful TMD and decrease its chronification risk.